Effects on p-type buffer layers for semitransparent organic photovoltaics using indium zinc oxide transparent electrode. (12th December 2019) - Kuwano, Kohei; Ogo, Hiroyuki; Chikamatsu, Masayuki; Yoshida, Yuji; Watanabe, Yasuyuki; Nishikawa, Eiichi
Abstract: The present study used transparent conductive oxide films as the top electrode of semitransparent organic photovoltaic (ST-OPV) cells. Indium zinc oxide (IZO) was fabricated by a facing direct current magnetron sputtering method for the top electrode of ST-OPV cells with an inverted structure, and then, the effect of selecting a p-type buffer material applicable to IZO films was investigated. Three kinds of p-type buffer materials were examined, namely, molybdenum trioxide (MoO3 ), tungsten trioxide-nanoparticles (WO3- NPs), and dipyrazino[2, 3-f:2′, 3′-h]quinoxaline-2, 3, 6, 7, 10, 11-hexacarbonitrile (HATCN). The MoO3 -, WO3 -, and HATCN-based cells yielded power conversion efficiencies (PCEs) of 4.02%, 3.60%, and 3.14%, respectively. After optimization of MoO3 thickness, the 15 nm thick MoO3 -based cell reached a PCE of 4.84% and a transmittance of 19.9% at a wavelength of 550 nm.